Cathode materials for secondary batteries
By using silicon oxide, free alkali metal, alkaline earth metal and post-transition metal doping elements as matrix in the silicon-based secondary battery cathode material, and dispersing silicon nanoparticles with residual compressive stress therein, the solution is solved The problem of deterioration of the characteristics of the existing silicon-based cathode materials during circulation is achieved, and high capacity and stable cycle characteristics are achieved.
Patent Information
- Application Number
- CN202110976523.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-30
- Filing Date
- 2021-08-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-08-24
AI Technical Summary
The existing silicon-based secondary battery cathode materials have problems such as insulation, particle disengagement and increased contact resistance during the charge and discharge cycle, resulting in a sharp deterioration of battery characteristics, and the initial charge and discharge efficiency and cycle characteristics are low, making it difficult to achieve commercialization.
The composite oxide containing silicon oxide, free alkali metal, alkaline earth metal and post-transition metal doping elements is used as the matrix, and silicon nanoparticles with residual compressive stress are dispersed and embedded in the matrix to form a co-uniform interface to improve mechanical properties and Electrochemical properties.
The electrochemical characteristics and mechanical properties of the secondary battery cathode material are significantly improved, high battery capacity, improved initial reversible efficiency and stable cycle characteristics are achieved, and the capacity retention rate at the commercial level is achieved.
Smart Images

Figure CN114447310B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a cathode material for a secondary battery, and more particularly to a cathode material for a secondary battery having improved capacity, initial efficiency and cycle characteristics. Background Art
[0002] In various industrial fields such as electronic products, electric / hybrid vehicles, aerospace / drone, etc., the demand for secondary batteries with long life, high energy density and high power density is increasing.
[0003] The typical commercial cathode material is graphite, but the theoretical maximum capacity of graphite does not exceed 372 mAh / g. Therefore, in order to realize high energy density secondary batteries, research is continuing on using chalcogens such as sulfur (maximum capacity 1675 mAh / g), silicon (maximum capacity 4200 mAh / g) or silicon oxide (maximum capacity 1500 mAh / g) and transition metal oxides as secondary battery cathode materials. Among many substances, silicon-based cathode materials are the most popular.
[0004] However, when particulate silicon is used as a cathode material, as the charge and discharge cycles are repeated, the battery characteristics deteriorate sharply due to the large volume change of silicon, resulting in insulation, particle detachment, and increased contact resistance. The battery may fail in less than 100 cycles. In the case of silicon oxide, lithium is lost due to the formation of irreversible products such as lithium silicate or lithium oxide, resulting in a sharp drop in initial charge and discharge efficiency.
[0005] In order to solve the above-mentioned problems of silicon-based cathode materials, technologies have been proposed to nano-scale silicon into wires and composite them with carbon materials, or to dope heterogeneous metals into silicon oxide to form a composite oxide phase, or to pre-lithiate silicon oxide, etc. However, the initial charge and discharge efficiency, cycle characteristics, or high-rate characteristics are still low, so it is still difficult to achieve commercialization.
[0006] Prior art literature
[0007] Patent Literature
[0008] Korean Patent Publication No. 10-2020-0065514
[0009] Korean Patent Publication No. 10-2015-0045336. Summary of the invention
[0010] An object of the present invention is to provide a cathode material for a silicon-based secondary battery having high battery capacity, improved initial reversible efficiency, and stable cycle characteristics.
[0011] According to one embodiment of the present invention, a cathode material for a secondary battery comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix and having residual compressive stress.
[0012] According to another embodiment of the present invention, a cathode material for a secondary battery comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix. The cathode material for a secondary battery satisfies the following formula 1:
[0013] Formula 1: 1<WN(Si) / WN(ref),
[0014] In Formula 1, WN(ref) is the center wave number of the Raman peak of bulk single crystal silicon, and WN(Si) is the center wave number of the Raman peak of nano-particulate silicon contained in the cathode material.
[0015] In the cathode material for a secondary battery according to an embodiment of the present invention, the difference between WN(Si) and WN(ref) may be 0.1 cm -1 above.
[0016] In the cathode material for a secondary battery according to an embodiment of the present invention, the full width at half maximum (FWHM) of the Raman peak of the nanoparticulate silicon contained in the cathode material may be greater than the full width at half maximum of the Raman peak of bulk single crystal silicon.
[0017] In the cathode material for a secondary battery according to an embodiment of the present invention, the full width at half maximum of the Raman peak of the nanoparticle-shaped silicon contained in the cathode material may be 4 cm -1 Up to 20cm -1 .
[0018] In the cathode material for a secondary battery according to one embodiment of the present invention, when a two-dimensional mapping analysis is performed based on the Raman signal of silicon, the difference between the maximum and minimum values of the offset specified by the following formula 2 under the following mapping conditions can be 5 cm -1 the following.
[0019] Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, irradiation time = 1 second (sec), focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1, map size = 14 μm × 14 μm,
[0020] Formula 2: Offset = WN i (Si)-WN(ref),
[0021] In formula 2, WN(ref) is the same as in formula 1, WN i (Si) is the center wave number of the Raman peak of nanoparticulate silicon contained in the cathode material in one pixel as a unit analysis area in mapping analysis.
[0022] According to another embodiment of the present invention, a cathode material for a secondary battery comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the above-mentioned matrix. The strength (hardness) of the above-mentioned cathode material for a secondary battery measured by a nanoindentation test can be above 4.0 GPa, and the Young's modulus (Young's modulus) can be above 40 MPa.
[0023] According to another embodiment of the present invention, the cathode material for secondary batteries comprises particles of the following substances: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the above-mentioned matrix, and the compressive strength of the particles can be above 100 MPa.
[0024] According to another embodiment of the present invention, a cathode material for a secondary battery comprises: a matrix, based on elemental composition, comprising silicon (Si), one or more doping elements (D) selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, and oxygen (O); and silicon nanoparticles dispersed and embedded in the matrix, wherein the cathode material for a secondary battery has a composition uniformity satisfying the following formula 3:
[0025] Formula 3: B / A≤0.30,
[0026] In Formula 3, A and B are respectively the average value (A) and standard deviation (B) of the content (weight percentage) of the doping element detected at any 100 points based on a cross section passing through the center of the cathode material.
[0027] In the cathode material for a secondary battery according to an embodiment of the present invention, based on the compound components, the matrix may include: silicon oxide; and a composite oxide of the doping element and silicon.
[0028] According to another embodiment of the present invention, a cathode material for a secondary battery comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix. When charged to 0.005V based on a cathode active material layer having a combination of 80 weight percent of an active material including a cathode material, 10 weight percent of a conductive material and 10 weight percent of a binder, the volume change of the cathode active material layer is within 60%.
[0029] According to another embodiment of the present invention, the cathode material for a secondary battery comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix. When a half-cell with a metal lithium foil as the electrode is charged and discharged under the following charge and discharge cycle conditions, the dQ / dV curve obtained has a value equivalent to Li 3.75 The lithium insertion peak of the Si reaction has a discharge capacity of more than 1200 mAh / g in the first charge and discharge cycle.
[0030] Charge and discharge cycle conditions: constant current / constant voltage (CC / CV), cut-off voltage (Cut-off) is 0.005V~1.0V, and charging rate (C-rate) is 0.5.
[0031] According to another embodiment of the present invention, silicon oxide, a cathode material for a secondary battery, comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the above-mentioned matrix, which satisfies Formula 4 when a charge and discharge test is carried out on a half-cell whose electrode is a metal lithium foil according to the following charge and discharge cycle conditions.
[0032] Charge and discharge cycle conditions: constant current / constant voltage, cut-off voltage of 0.005V~1.0V, charging rate of 0.5.
[0033] Formula 4: 95% ≤ C50 / C1×100,
[0034] In Formula 4, C1 is the discharge capacity (mAh / g) in the first charge-discharge cycle, and C50 is the discharge capacity in the 50th charge-discharge cycle.
[0035] In the cathode material for a secondary battery according to an embodiment of the present invention, C50 may be greater than 1200 mAh / g.
[0036] In the cathode material for a secondary battery according to an embodiment of the present invention, the average diameter of the silicon nanoparticles may be 2 nm to 30 nm.
[0037] In the cathode material for a secondary battery according to an embodiment of the present invention, the interface between the silicon nanoparticles and the matrix may be a coherent interface.
[0038] In the cathode material for a secondary battery according to an embodiment of the present invention, the matrix may further include a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals.
[0039] In the cathode material for a secondary battery of one embodiment of the present invention, the doping element may be one or more selected from lithium (Li), sodium (Na), potassium (K), aluminum (Al), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba).
[0040] In the secondary battery cathode material according to one embodiment of the present invention, the composite oxide may include crystals.
[0041] In the cathode material for a secondary battery according to an embodiment of the present invention, the cathode material may have an average diameter of 10 0 μm level (order) to 10 1 μm-level particles.
[0042] In the cathode material for a secondary battery according to an embodiment of the present invention, the cathode material may further include a coating layer containing carbon.
[0043] The present invention includes a cathode comprising the above-mentioned cathode material for a secondary battery.
[0044] The present invention includes a secondary battery comprising the above cathode.
[0045] The cathode material for secondary batteries of the present invention comprises a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and embedded in the matrix and having residual compressive stress, thereby improving mechanical and electrochemical properties. In particular, a secondary battery containing the silicon-based cathode material has a capacity retention rate at a practical commercial level while having a relatively high discharge capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 FIG. 1 is a diagram showing the energy dispersive X-ray spectroscopy (EDS) line profile of Mg in a cross section of a cathode material prepared according to an embodiment of the present invention.
[0047] Figure 2The figure is a diagram for detecting and showing the Raman spectrum of the cathode material prepared according to one embodiment of the present invention.
[0048] Figure 3 This is a diagram showing the result of two-dimensional mapping of a cathode material prepared according to an embodiment of the present invention based on the Raman signal of silicon.
[0049] Figure 4 The figure is used to detect and show the strength and Young's modulus of the cathode material prepared according to one embodiment of the present invention.
[0050] Figure 5 A graph is provided to detect and illustrate the battery capacity according to the charge and discharge cycles of a half-cell having a cathode including a cathode material prepared according to an embodiment of the present invention.
[0051] Figure 6 A high-resolution transmission electron microscope photograph of a cathode material prepared according to an embodiment of the present invention.
[0052] Figure 7 A high-resolution transmission electron microscope photograph of a cathode material substrate prepared according to an embodiment of the present invention and a selected area diffraction pattern (SADP) of the substrate are shown.
[0053] Figure 8 The present invention is a scanning electron microscope photograph of a cathode including a cathode material prepared according to an embodiment of the present invention to observe a cross section and thickness of the cathode before lithiation and a cross section and thickness of cathode lithium after lithiation.
[0054] Fig. 9 The figure is a graph measuring and showing the particle size distribution of cathode material powder prepared according to one embodiment of the present invention.
[0055] Fig.10 FIG. 5 is a dQ / dV curve of a half-cell having a cathode including a cathode material prepared according to an embodiment of the present invention.
[0056] Fig.11 FIG. 4 is a diagram showing a selected area diffraction pattern of a cathode material prepared according to an embodiment of the present invention in a charged state. DETAILED DESCRIPTION
[0057] Hereinafter, the cathode material for secondary batteries of the present invention will be described in detail with reference to the accompanying drawings. The accompanying drawings introduced below are provided to fully convey the idea of the present invention to ordinary technicians in the technical field to which the present invention belongs. Therefore, the present invention is not limited to the accompanying drawings provided below, but can also be embodied in other forms. The accompanying drawings provided below can be exaggerated to clarify the idea of the present invention. In the absence of other definitions, all terms including technical terms or scientific terms used in this specification have the same meaning as those commonly understood by ordinary technicians in the technical field to which the present invention belongs. In the following description and drawings, the description of known functions and structures that may unnecessarily confuse the gist of the present invention will be omitted.
[0058] Furthermore, in the specification and the appended claims, a singular form may include a plural form unless the context clearly indicates a different meaning.
[0059] In this specification and the appended claims, the terms “first”, “second”, etc. do not have limiting meanings but are used for the purpose of distinguishing one structural element from other structural elements.
[0060] In this specification and the appended claims, terms such as “including” or “having” are intended to specify the presence of features or structural elements recorded in the specification, and unless otherwise specified, do not preclude the possibility of the addition of one or more other features or structural elements.
[0061] In this specification and the scope of protection of the accompanying invention claims, when a film (layer), region, structural element, etc. is said to be located on top of or above other parts, it not only refers to the situation where it is in contact with other parts and directly located on them, but also includes the situation where other films (layers), regions, structural elements, etc. are interposed between them.
[0062] The applicant has found that in a silicon-based cathode material composed of a composite of silicon and silicon oxide, the mechanical and electrochemical properties of the cathode material are significantly affected by the residual stress of the silicon contained in the cathode material. Based on the above findings, the applicant has conducted in-depth research and found that when silicon is dispersed in a silicon oxide-based matrix in the form of nanoparticles and has residual compressive stress, the mechanical and electrochemical properties of the cathode material are significantly improved, thereby completing the present invention.
[0063] Therefore, the cathode material of the present invention based on the above-mentioned discovery exhibits mechanical and electrochemical properties that cannot be obtained in existing silicon-based cathode materials through the combination of silicon dispersed in the form of nanoparticles and having residual compressive stress and a matrix. Therefore, the present invention includes multiple embodiments based on the properties of the silicon-based cathode material of the present invention.
[0064] In the present invention, the matrix may refer to a solid medium in which nanoparticle-shaped silicon is dispersed, or may refer to a substance that forms a continuous phase (continuum) relative to silicon nanoparticles as a dispersed phase in the cathode material. In the present invention, the matrix may refer to one or more substances other than metallic silicon (Si) in the cathode material.
[0065] In the present invention, nanoparticles may refer to particles with a size (diameter) of 10 0 Nanoscale to 10 2 The nanometer-scale particles have a diameter of 500 nm or less, specifically 200 nm or less, more specifically 100 nm or less, and even more specifically 50 nm or less.
[0066] In the present invention, the cathode material for secondary batteries includes, but is not limited to, cathode materials for lithium secondary batteries. The cathode material of the present invention can be used as an active material for secondary batteries such as sodium batteries, aluminum batteries, magnesium batteries, calcium batteries, and zinc batteries, and can be used in other existing energy storage / generation devices using silicon-based materials such as supercapacitors, dye-sensitized solar cells, and fuel cells.
[0067] The cathode material for a secondary battery of one embodiment (I) of the present invention comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix. The cathode material for a secondary battery satisfies the following formula 1:
[0068] Formula 1: 1<WN(Si) / WN(ref),
[0069] In Formula 1, WN(ref) is the center wave number of the Raman peak of bulk single crystal silicon, and WN(Si) is the center wave number of the Raman peak of nano-particulate silicon contained in the cathode material.
[0070] In Formula 1, the ratio of the central wavenumber of the Raman peak of bulk single crystal silicon to the central wavenumber of the Raman peak of nanoparticle silicon contained in the cathode material is a parameter representing the type of stress (residual stress) remaining in the silicon nanoparticles dispersed and embedded in the matrix and the magnitude of the residual stress.
[0071] In Formula 1, the term "bulk single crystal silicon" should be interpreted as silicon having a size that substantially exhibits the physical properties of bulk single crystal silicon. From the perspective of ensuring a clear comparison benchmark and purchasing convenience, bulk single crystal silicon refers to a single crystal silicon wafer having a sub-millimeter-order horizontal thickness, and as a specific example, may refer to a single crystal silicon wafer having a thickness of 0.4 mm to 0.7 mm.
[0072] In Formula 1, WN(Si) / WN(ref) greater than 1 means that the central wavenumber of the Raman peak of the nano-granular silicon contained in the cathode material shifts to a longer wavenumber (a shorter wavelength in the wavelength of Raman scattered light) compared to bulk single crystal silicon, which means that the nano-granular silicon has residual compressive stress.
[0073] In Formula 1, the Raman peak of silicon in bulk single crystal silicon and nanoparticle silicon may refer to the peak at 500 cm -1 Up to 540cm -1 The Raman peak in the region can be specifically referred to as the peak at 510 cm -1 Up to 530cm -1 The Raman peak in the region, more specifically, can refer to the peak at 515 cm -1 Up to 528cm -1 The central wave number of the peak, that is, the wave number corresponding to the center of the peak, may refer to the wave number with the maximum intensity value in the peak. In this case, if there are more than two Raman peaks in the Raman shift region, the peak with the largest intensity corresponds to the Raman peak of silicon of Formula 1, and if more than two Raman peaks are in the form of overlapping double peaks, the wave number with the maximum intensity value in the peak with the larger intensity in the double peak may correspond to the central wave number of the peak.
[0074] The difference between WN(Si) and WN(ref) (WN(Si)-WN(ref)) is a parameter that directly indicates the magnitude of the residual compressive stress of silicon nanoparticles. Specifically, the difference between WN(Si) and WN(ref) can be 0.1 cm -1 Above, 0.2cm -1 Above, 0.3cm -1 Above, 0.4cm -1 Above, 0.5cm -1 Above, 0.6cm -1 Above, 0.7cm -1 Above, 0.8cm -1 Above, 0.9cm -1 Above, 1.0cm -1 Above, 1.1cm -1 Above, 1.2cm -1 Above, 1.3cm -1 Above, 1.4cm -1 Above, 1.5cm -1 Above, 1.6cm -1 Above, 1.7cm -1 Above, 1.8cm -1 Above, 1.9cm -1 Above, 2.0cm-1 Above, 2.1cm -1 Above, 2.2cm -1 Above, 2.3cm -1 Above, 2.4cm -1 Above, 2.5cm -1 Above, 2.6cm -1 Above, 2.7cm -1 Above, 2.8cm -1 Above, 2.9cm -1 Above, 3.0cm -1 Above, 3.1cm -1 Above, 3.2cm -1 Above, 3.3cm -1 Above, 3.4cm -1 Above, 3.5cm -1 Above, 3.6cm -1 Above, 3.7cm -1 Above, 3.8cm -1 Above, 3.9cm -1 Above or 4.0cm -1 Above, it can be 6.0cm -1 Below, more substantially, can be 5.5cm -1 the following.
[0075] While satisfying the above-mentioned condition of the difference between the central wavelengths of the Raman peaks of the bulk single crystal silicon and the nano-particle silicon contained in the cathode material, or independently, the half-maximum full width of the Raman peak of the nano-particle silicon contained in the cathode material can be larger than the half-maximum full width of the Raman peak of the bulk single crystal silicon. The half-maximum full width value larger than that of the bulk single crystal silicon can be caused by the structure in which the silicon contained in the cathode material is dispersed in the form of extremely fine silicon particles and embedded in the matrix. Specifically, the half-maximum full width of the Raman peak of the nano-particle silicon contained in the cathode material can be 4cm -1 Up to 20cm -1 、6cm -1 Up to 20cm -1 、6cm -1 Up to 18cm -1 、6cm -1 Up to 16cm -1 、8cm -1 Up to 20cm -1 、8cm -1 Up to 18cm -1 、8cm -1 Up to 16cm -1 、10cm -1 Up to 20cm -1 、10cm -1 Up to 18cm-1 or 10cm -1 Up to 16cm -1 , but is not limited to this.
[0076] When the above conditions are met simultaneously or independently, the central wave number of the Raman peak of silicon is used as the reference (0 cm -1 ), the nanoparticle-shaped silicon contained in the cathode material is +20cm in the Raman spectral phase reference -1 The intensity (I1) of the position (wave number) is consistent with the -20cm in the Raman spectrum. -1 The intensity (I2) of the position (wave number) can be significantly different, -20cm -1 The intensity (I2) of the position (wave number) can be compared with +20cm -1 The intensity (I1) of the position (wave number) is large. In this case, significantly different can mean that the ratio of I2 / I1 is greater than 1.20. The asymmetry of the Raman peak of silicon (the long tail extending in the short wave number direction) can also be caused by the structure of silicon nanoparticles with residual compressive stress dispersed and embedded in the matrix.
[0077] While satisfying the above conditions, when the cathode material is subjected to two-dimensional mapping analysis based on the Raman signal of silicon, the difference between the maximum and minimum values of the offset specified by the following formula 2 can be 5 cm -1 the following.
[0078] Formula 2: Offset = WN i (Si)-WN(ref)
[0079] In formula 2, WN(ref) is the same as in formula 1, WN i (Si) is the center wave number of the Raman peak of nanoparticle-shaped silicon contained in the cathode material in one pixel as a unit analysis area during mapping analysis. In this case, the shift according to Formula 2 can be calculated for each pixel of the silicon Raman signal in the two-dimensional Raman map obtained by the two-dimensional mapping analysis, and the maximum value and the minimum value are of course the minimum value and the maximum value in the shift calculated according to Formula 2.
[0080] Based on the two-dimensional Raman map of silicon obtained by two-dimensional mapping analysis of the cathode material based on the Raman signal of silicon, the difference between the maximum and minimum values of the peak center wave number shift value (offset) of silicon compared to bulk single crystal silicon according to Formula 2 is an indicator of the uniformity of the residual compressive stress of silicon nanoparticles dispersed and embedded in the cathode material. The difference between the maximum and minimum values of the offset based on the two-dimensional Raman map can meet 5.0 cm -1 Below, 4.5cm -1 Below, 4.0cm -1 Below, 3.5cm -1Below, 3.0cm -1 Below, 2.5cm -1 Below or 1.0cm -1 Below, in fact, the difference between the maximum and minimum values can meet 0.1cm -1 Above, more substantially, can meet 0.5cm -1 The difference between the maximum value and the minimum value mentioned above means that most of the silicon nanoparticles contained in the cathode material have residual compressive stress, which in essence means that all the silicon nanoparticles have residual compressive stress, and further means that the residual compressive stress of most of the silicon nanoparticles contained in the cathode material is almost the same, which in essence means that the residual compressive stress of all the silicon nanoparticles is almost the same.
[0081] In the experiment, the Raman spectrum of silicon contained in the cathode material can be measured at room temperature (20°C to 25°C) and atmospheric pressure with an excitation laser wavelength of 532nm, a laser power of 0.5mW, and a spectrometer resolution of 1cm -1 The detection was carried out under the conditions of 1g cathode material and 15s detector exposure time.
[0082] In the experiment, the 2D Raman mapping of the cathode material using the Raman signal of silicon can be performed with the following conditions: excitation laser wavelength = 532nm, laser power = 0.1mW, detector exposure time (exposure time per unit analysis area) = 1 second, focal length = 30mm, grating = 1800grooves / mm, pixel resolution = 1cm -1 , mapping size = 14μm×14μm mapping conditions, can be detected at room temperature and atmospheric pressure.
[0083] According to another embodiment (II) of the present invention, the cathode material for secondary batteries comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix, and the cathode material for secondary batteries has a strength of 4.0 GPa or more and a Young's modulus of 40 MPa or more as measured by a nanoindentation test. In the following, regarding the mechanical properties of the cathode material for secondary batteries, all properties represent properties at room temperature (20°C to 25°C) unless the temperature is specifically limited.
[0084] Nanoindentation testing can be performed according to ASTM E2546, ISO 14577-1E, ISO 14577-2E, and ISO 14577-3E, and the Young's modulus E can be calculated according to a well-known formula. Wherein, E* represents the Young's modulus of the indenter, and ν is the Poisson's ratio of the Berkovich indenter assumed to be 0.3. The nanoindentation test using the Berkovich indenter can be performed under the conditions of a maximum load of 50 mN and a load application speed of 100 mN / minute (min). The strength and Young's modulus detected by the nanoindentation test can be the average value of the physical property values obtained by performing nanoindentation testing in a matrix form of 5×5 to 25×25, based on the indentation caused by the indenter, so that the distance between the indentations moves is at least 10 μm. In this case, the cathode material sample for the nanoindentation test can be prepared by polishing after installing a plate-shaped block cathode material.
[0085] Specifically, the strength (indentation strength) of the cathode material for secondary batteries tested by nanoindentation can be 4.0 GPa or more, 4.5 GPa or more, 5.0 GPa or more, 5.5 GPa or more, 6.0 GPa or more, 6.5 GPa or more, 7.0 GPa or more, 7.5 GPa or more, 8.0 GPa or more, 8.5 GPa or more, 9.0 GPa or more, 9.5 GPa or more, 10.0 GPa or more, 10.2 GPa or more, 10.4 GPa or more. Above, above 10.6 GPa, above 10.8 GPa, above 11.0 GPa, above 11.2 GPa, above 11.4 GPa, above 11.6 GPa, above 11.8 GPa, above 12.0 GPa, above 12.2 GPa, above 12.4 GPa, above 12.6 GPa, above 12.8 GPa or above 13.0 GPa, and in substance, can be below 25.0 GPa, and more in substance, can be below 20.0 GPa. While meeting the above conditions, the Young's modulus of the cathode material for secondary batteries tested by nanoindentation can be above 40MPa, above 45MPa, above 50MPa, above 55MPa, above 60MPa, above 65MPa, above 70MPa, above 75MPa, above 80MPa, above 85MPa, above 90MPa, above 92MPa, above 94MPa, above 96MPa, above 98MPa, above 100MPa, above 102MPa, above 104MPa, above 106MPa, above 08MPa, above 110MPa, above 112MPa, above 114MPa, above 116MPa, above 118MPa or above 120MPa. In essence, it can be below 250MPa, and more substantially, it can be below 200MPa.
[0086] The mechanical properties of the cathode material measured by nanoindentation testing are physical property values that can be achieved by residual stress existing in the cathode material, including residual compressive stress of nanoparticle-shaped silicon.
[0087] A cathode material with high strength and excellent elasticity means that the particulate cathode material will not be physically damaged during the electrode preparation process, and can also prevent damage to the electrode (cathode) pore structure. It also means that stable and uniform contact with the electrolyte can be ensured. The traditional secondary battery field has established an electrode preparation process consisting of cathode material slurry preparation - slurry coating and drying on the collector - calendering (calendering).
[0088] According to another embodiment of the present invention (III), the cathode material for a secondary battery is in the form of particles comprising the following substances: a matrix containing silicon oxide, a composite oxide of silicon with one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the above-mentioned matrix. The compressive strength (St) of the particles can be more than 100 MPa. The compressive strength St of the particles can be calculated by a well-known formula, where P is the applied force, d is the particle size of the particles, and L is the distance, which can be measured using a micro compression tester (e.g., MCT-W500-E, Shimadzu Corporation).
[0089] Specifically, the particle compressive strength of the granular cathode material for secondary batteries can be above 100 MPa, above 105 MPa, above 110 MPa, above 115 MPa, above 120 MPa, above 125 MPa, above 130 MPa, above 135 MPa, above 140 MPa, above 145 MPa, above 150 MPa, above 155 MPa or above 160 MPa, and in substance, it can be below 250 MPa, and more in substance, it can be below 200 MPa.
[0090] The mechanical properties of the cathode material are physical properties that can be achieved by the residual stress present in the cathode material, including the residual compressive stress of the silicon nanoparticles. Furthermore, a stress field can be formed in the matrix that encapsulates the silicon nanoparticles with the residual compressive stress through the coherent interface between the silicon nanoparticles and the matrix, thereby further improving the mechanical strength and elasticity.
[0091] According to another embodiment (IV) of the present invention, a cathode material for a secondary battery comprises: a matrix, based on elemental composition, comprising silicon, one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, and oxygen; and silicon nanoparticles dispersed and embedded in the matrix. The cathode material for a secondary battery has a composition uniformity that satisfies the following formula 3.
[0092] Formula 3: B / A≤0.30
[0093] In Formula 3, A and B are respectively the average value (A) and standard deviation (B) of the content (weight percentage) of the doping element detected at any 100 points based on the cross section passing through the center of the cathode material. Specifically, A and B can be the average content (weight percentage, A) and standard deviation (B) of the doping element calculated from 100 points selected from the line profile of the doping element passing through the center of the cross section of the cathode material.
[0094] More specifically, B / A of Formula 3 may satisfy 0.30 or less, 0.25 or less, 0.20 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, or 0.11 or less.
[0095] In Formula 3, B / A is a parameter representing the composition uniformity of the cathode material based on the doping element (D). The cathode material can exhibit uniform mechanical and electrochemical properties by satisfying the excellent composition uniformity of B / A in the above range.
[0096] In the experiment, the content of doping elements or spectral line profile analysis can be performed using an electron probe microanalyzer (EPMA) or energy dispersive X-ray spectroscopy (EDS) provided by a transmission electron microscope or a scanning electron microscope, but is not limited to these.
[0097] In the cathode material for secondary batteries that satisfies the above-mentioned composition uniformity, based on the element composition, the matrix may include silicon, one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, silicon and oxygen, and based on the compound composition, the matrix may include silicon oxide and a composite oxide of the doping element and silicon. Therefore, the composition uniformity of the doping element specified by Formula 3 may correspond to the composition uniformity of the composite oxide, but is not limited thereto.
[0098] According to another embodiment (V) of the present invention, the cathode material for secondary batteries comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix. When the cathode active material layer (hereinafter referred to as the reference active material layer) having a combination of 80 weight percent of active material containing cathode material, 10 weight percent of conductive material and 10 weight percent of binder is charged to 0.005V, the volume change of the cathode active material layer is within 60%. In this case, the volume change (%) of the cathode active material layer (reference active material layer) can be defined as "(thickness of the reference active material layer after lithiation - thickness of the reference active material layer before lithiation) / thickness of the reference active material layer before lithiation × 100". In the experiment, the thickness of each reference active material layer before and after lithiation can be measured by scanning electron microscope observation photos, etc.
[0099] When charged to 0.005V, the volume change is within 60%, specifically, only within 50%, within 40%, within 30%, within 25% or within 20%, which means that the volume change is significantly reduced compared with the existing silicon-based cathode materials, which means that the main problems of the existing silicon-based cathode materials are greatly improved.
[0100] The reference active material layer as a benchmark for testing the volume expansion of the cathode material may include 80 weight percent of the active material and conductive material containing the above-mentioned cathode material, specifically, 10 weight percent of carbon black, 10 weight percent of a binder, specifically, 5 weight percent of carboxymethyl cellulose and 5 weight percent of styrene butadiene rubber. In this case, the active material may include only the above-mentioned cathode material, or a mixture of the above-mentioned cathode material and a carbon-based cathode active material (such as graphite). In the case where the active material includes a mixture, the weight percentage of the cathode material may be at a level of 5 weight percent to 90 weight percent based on the total weight of the mixture (100%). In a cathode having a reference active material layer (reference cathode), the collector may be copper foil. The thickness of the reference active material layer before lithiation may be 15 μm to 25 μm, but is not limited thereto.
[0101] The charging of the reference active material layer can be carried out using a half-cell (such as a CR2032 button half-cell) having a cathode of the reference active material layer (reference cathode) and a counter electrode as a metal lithium foil, according to the charge and discharge test under the following charge and discharge cycle conditions. In the charge and discharge cycle, specifically, it can be charged to 0.005V in the first charge and discharge cycle.
[0102] Charge and discharge cycle conditions: constant current / constant voltage, cut-off voltage of 0.005V~1.0V, charging rate of 0.5.
[0103] Hereinafter, unless otherwise specified, the electrochemical characteristics (charge and discharge characteristics, discharge capacity, dQ / dV curve, etc.) of the cathode material including the volume change during the above-mentioned lithiation can be the electrochemical characteristics of a half-cell including a cathode of the cathode material and a counter electrode of a metal lithium foil, and can be the electrochemical characteristics of a half-cell after a formation process. Therefore, when referring to the charging of the active material layer, the first cycle according to the proposed charge and discharge cycle conditions also refers to the first cycle after the formation process. The half-cell can be a battery comprising the following substances: a cathode including a cathode collector and a cathode active material layer located on at least one side of the collector and containing a cathode material of an embodiment of the present invention; a counter electrode as a metal lithium foil; a separation membrane between the cathode and the counter electrode; and an electrolyte, which is prepared by dissolving LiPF6 at a concentration of 1M in a mixed solvent of ethylene carbonate and diethyl carbonate mixed in a volume ratio of 1:1. The formation process may include a primary process of charging and discharging under the conditions of constant current / constant voltage, a cut-off voltage of 0.005V~1.5V, and a charging rate of 0.1, and a secondary process of charging and discharging under the conditions of constant current / constant voltage, a cut-off voltage of 0.005V~1.0V, and a charging rate of 0.1. However, the present invention is not limited by the formation process conditions of the test battery (half-cell), as long as it is an existing formation process commonly performed in a battery for testing the electrochemical properties of the cathode material.
[0104] According to another embodiment (VI) of the present invention, the cathode material for a secondary battery comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix. When a half-cell with a metal lithium foil as the electrode is charged and discharged according to the following charge and discharge cycle conditions, the dQ / dV curve obtained has a value equivalent to Li 3.75 The lithium insertion peak of the Si reaction has a discharge capacity of more than 1200 mAh / g in the first charge and discharge cycle.
[0105] Charge and discharge cycle conditions: constant current / constant voltage, cut-off voltage of 0.005V~1.0V, charging rate of 0.5.
[0106] The dQ / dV graph may be a graph showing the relationship between the differential value dQ / dV obtained by differentiating the battery capacity (discharge capacity) Q in the first charge and discharge cycle with respect to the potential V of the cathode based on the metal lithium foil of the half-cell and the potential V. In this case, the dQ / dV graph corresponds to Li 3.75The lithium insertion peak of the Si reaction may refer to a peak located in a voltage range of 0.005V to 0.100V, specifically, may refer to a peak located in a voltage range of 0.005V to 0.050V, and more specifically, may refer to a peak located in a voltage range of 0.005V to 0.040V.
[0107] That is, the cathode material for a secondary battery according to another embodiment (VI) of the present invention achieves lithium insertion exceeding Li 3.5 Si to reach Li 3.75 Si. With the realization of lithium insertion to reach Li 3.75 Si can increase the capacity of the cathode material. As a substantial example, when charged and discharged under the above-mentioned charge and discharge cycle conditions, the discharge capacity C1 of the half-cell after the formation process in the first charge and discharge cycle can be 1200mAh / g or more, 1250mAh / g or more, 1300mAh / g or more, 1350mAh / g or more, 1400mAh / g or more, 1450mAh / g or more, or 1500mAh / g or more, and in essence, can be 2500mAh / g or less.
[0108] According to another embodiment (VII) of the present invention, the cathode material for a secondary battery comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the matrix. When a charge and discharge test is performed using a half-cell whose electrode is a metal lithium foil according to the following charge and discharge cycle conditions, Formula 4 is satisfied.
[0109] Charge and discharge cycle conditions: constant current / constant voltage, cut-off voltage of 0.005V~1.0V, charging rate of 0.5.
[0110] Formula 4: 95% ≤ C50 / C1×100
[0111] In Formula 4, C1 is the discharge capacity (mAh / g) in the first charge-discharge cycle, and C50 is the discharge capacity in the 50th charge-discharge cycle.
[0112] Specifically, C50 / C1×100 can be 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more. This cycle characteristic means that the storage / release of lithium ions in the cathode material is substantially completely reversible, which means that during 50 repeated charge and discharge processes, there is substantially no capacity reduction (deterioration of the cathode material, reduction of electrical contact of the cathode material in the cathode active material layer, generation of irreversible products, etc.), which means that it has an extremely excellent capacity retention rate.
[0113] As an example, C50 may be 1200 mAh / g or more, 1250 mAh / g or more, 1300 mAh / g or more, 1350 mAh / g or more, 1400 mAh / g or more, 1450 mAh / g or more, or 1500 mAh / g or more. In practice, it may be 2500 mAh / g or less.
[0114] According to another embodiment (VIII) of the present invention, the cathode material for secondary batteries comprises: a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and embedded in the above-mentioned matrix and having residual compressive stress.
[0115] By dispersing the residual compressive stress of nanoparticle-like silicon embedded in the matrix, and further, forming a stress field in the matrix around the silicon nanoparticles through the residual compressive stress of silicon and the coherent interface formed between the silicon nanoparticles and the matrix, the physical properties of the cathode material or measurable parameters can be shown by one embodiment of the cathode material based on Raman spectroscopy, another embodiment of the cathode material based on mechanical properties, and another embodiment of the cathode material based on electrochemical properties during lithiation as described above.
[0116] In the present invention, the cathode material may satisfy one or more embodiments, two or more embodiments, three or more embodiments, four or more embodiments, five or more embodiments, six or more embodiments, seven or more embodiments among the above-mentioned embodiments (I to VIII) or satisfy all embodiments I to VIII.
[0117] In the following, unless “one embodiment of the present invention” is particularly limited and described, the content described below is equivalent to each of all the embodiments provided by the present invention.
[0118] In a specific example, based on the elemental composition, the cathode material may include silicon, oxygen, and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals. Silicon may include silicon components in the state of elemental silicon and silicon components in the state of oxides, and the silicon components in the state of oxides may include an oxide state containing only silicon, a composite oxide state containing silicon and doping elements, or all of them. The doping element may include a doping element component in the state of oxides, and the doping element in the state of oxides may include an oxide state containing only the doping element, a composite oxide state containing silicon and doping elements, or all of them.
[0119] Based on the compound composition, the cathode material may include silicon oxide, a composite oxide of a doping element and silicon, or a mixture thereof, and may also include elemental silicon. Silicon oxide is SiOx, x may include a real number from 0.1 to 2, and the composite oxide is D l Si m O n , D is a doping element, l can be a real number of 1 to 6, m can be a real number of 0.5 to 2, and n can be a real number that satisfies electrical neutrality according to the oxidation numbers of D and Si, L, and m. As an example, when D is Mg, the composite oxide can include one or more oxides selected from MgSiO3 and Mg2SiO4, etc., but in the present invention, D and the composite oxide are not limited to oxides between Mg and Mg-Si.
[0120] Based on the microstructure, the cathode material may include a dispersed phase, the dispersed phase includes a matrix and silicon nanoparticles, the matrix includes silicon oxide, a composite oxide of one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals and silicon, or a mixture thereof. The dispersed phase may be uniformly dispersed and embedded in the matrix.
[0121] In a specific example, the silicon nanoparticles may be crystalline, amorphous, or a composite phase in which crystalline and amorphous are mixed. In essence, the silicon nanoparticles may be crystalline.
[0122] In a specific example, the matrix can be a crystalline, amorphous, or a composite phase in which crystalline and amorphous are mixed. In detail, the matrix can be a crystalline or a composite phase in which crystalline and amorphous are mixed. Specifically, the matrix can include amorphous, crystalline, or amorphous and crystalline silicon oxides and crystalline composite oxides.
[0123] The interface between the silicon nanoparticles and the substrate may include a coherent interface, an incoherent interface, a semi-coherent interface, and in essence, may include a coherent interface or a semi-coherent interface, and more in essence, may include a coherent interface. As is well known, a coherent interface is an interface where the lattices of the two materials constituting the interface maintain lattice continuity at the interface, and a semi-coherent interface has a portion of lattice inconsistency, and the above-mentioned lattice inconsistency portion can be regarded as an interface with defects such as electric potential. Therefore, in a cathode material having a coherent or semi-coherent interface between the silicon nanoparticles and the substrate, the substrate region in contact with the silicon nanoparticles may be a crystal, specifically, a crystalline silicon oxide, a crystalline composite oxide, or a mixture thereof. In the experiment, the interface structure of the coherent interface, the incoherent interface, and the semi-coherent interface can be distinguished by high-resolution scanning electron microscopy observation, etc., which is well known to those of ordinary skill in the art to which the present invention belongs.
[0124] In one embodiment, the average diameter of the silicon nanoparticles may be 10 0 Nanoscale to 10 1 Nanoscale, specifically, can be 1nm to 50nm, 2nm to 40nm, 2nm to 35nm, 2nmnm to 30nm, 2nmnm to 20nm or 2nm to 15nm, but is not limited thereto. However, the silicon nanoparticles at the level below 30nm form a coherent interface with the matrix as a whole, and can form stress in a wider region on the matrix through the compressive stress remaining in the silicon nanoparticles, so it is more advantageous. In the experiment, the average diameter of the silicon nanoparticles can be measured by observing the image with a transmission electron microscope to measure the size of the silicon nanoparticles in the cathode material, and the average value of the size of more than 10, more than 20 or more than 30 silicon nanoparticles can be calculated to calculate.
[0125] In a specific example, the doping element can be one or more selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn) and bismuth (Bi). Therefore, the composite oxide can be an oxide between silicon and one or more elements selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn) and bismuth (Bi). Through the synergistic effect between the composite oxide and the silicon nanoparticles with residual compressive stress, the mechanical properties and electrochemical properties of the cathode material can be further improved. In order to facilitate the formation of a coherent interface with silicon nanoparticles, the doping element can be an element selected from the group consisting of alkali metals and alkaline earth metals, specifically, it can be one or more elements selected from lithium, sodium, potassium, rubidium, cesium, beryllium, magnesium, calcium, strontium and barium, more preferably, it can be one or more elements selected from alkaline earth metals, specifically, it can be one or more elements selected from magnesium, calcium, strontium and barium. Most preferably, from the perspective of easy formation of a coherent interface and synergistic effect with silicon nanoparticles having residual compressive stress, the doping element can include magnesium. As described above, the doping element can be included in the cathode material in the form of a composite oxide with silicon and / or in the form of an oxide of the doping element, and can be mainly included in the cathode material in the form of a composite oxide. Specifically, in the case where the matrix contains a doping element in the form of a composite oxide with silicon, the composite oxide can contain crystals, and more substantially, the composite oxide can be crystalline. Therefore, the matrix can contain a crystalline composite oxide.
[0126] In one specific example, the silicon oxide contained in the matrix may be SiO x, wherein x may satisfy a real number of 0.1 to 2, more specifically, may satisfy a real number of 0.5 to 2, and may include a first silicon oxide and a second silicon oxide having different x. As a substantial example, the silicon oxide included in the matrix may include SiO x1 (x1 is a real number from 1.8 to 2) of the first silicon oxide and SiO x2 (x2 is a real number ranging from 0.8 to 1.2) The second silicon oxide. The silicon oxide contained in the matrix may be crystalline, amorphous, or a composite phase of crystalline and amorphous. In essence, it may be amorphous.
[0127] In one embodiment, the cathode material may include 15 weight percent to 50 weight percent of nano-particle silicon and the remainder of the matrix.
[0128] In a specific example, the matrix of the cathode material may contain silicon oxide and composite oxide at the same time. When the matrix is based on 100 parts by weight of silicon oxide, the weight of the composite oxide is set to A. When the concentration of the doping element in the cathode material is set to B based on weight percentage, A / B may satisfy 2 to 50, 2 to 40, 2 to 30 or 2 to 20.
[0129] In a specific example, the cathode material may be in a particle form. The particle-shaped cathode material may have a particle size generally required for use in a secondary battery, and as an example, may have a particle size of 10 0 μm to 10 1 The average diameter of the μm level may be, specifically, 5 μm to 30 μm, but is not limited thereto.
[0130] In a specific example, the cathode material may further include a coating layer containing carbon, specifically, a surface coating layer coated on the surface of the cathode material. The surface coating layer can improve the electrical properties of the cathode material, which is advantageous. The thickness of the coating layer can be in the range of 2 nm to 30 nm, but is not limited thereto.
[0131] In one specific example, the cathode material includes silicon nanoparticles having residual compressive stress, and when electrochemically alloyed with lithium (lithiation), it can have an alloying ratio of 3.5 (greater than) moles to 3.75 moles of lithium per mole of silicon, and specifically, it can have an alloying ratio of 3.6 moles to 3.75 moles of lithium per mole of silicon. Such a high alloying ratio is very conducive to high capacity. In addition, in one specific example, the cathode material can have the characteristics of high initial charge and discharge efficiency and capacity retention rate.
[0132] The present invention includes a cathode comprising the above-mentioned cathode material. The cathode may be a cathode of a secondary battery, specifically, a cathode of a lithium secondary battery. The cathode may include: a current collector; and a cathode active material layer located on at least one side of the current collector and comprising the above-mentioned cathode material. As required, the cathode active material layer may also include a binder and a conductive material commonly used in cathode materials and secondary battery cathodes.
[0133] The present invention includes a secondary battery including the above-mentioned cathode. Specifically, the present invention includes a lithium secondary battery including the above-mentioned cathode. The lithium secondary battery may include: an anode including an anode current collector and an anode active material layer located on at least one side of the anode current collector; the above-mentioned cathode; a separation membrane between the anode and the cathode; and an electrolyte that conducts lithium ions. The anode current collector, the cathode current collector, the anode active material of the anode active material layer or a combination thereof, the separation membrane and the electrolyte solvent, or the electrolyte salt or the concentration of the electrolyte salt, etc., as long as they are substances or combinations commonly used in lithium secondary batteries.
[0134] Example
[0135] The raw materials of Si, SiO2 and MgO were respectively put into a powder mixer at a molar ratio of 6 (Si): 4.5 (SiO2): 1.5 (MgO), and then uniformly mixed to prepare the raw materials.
[0136] 26 kg of the above raw materials were placed in a crucible in a vacuum chamber of 0.1 torr or less, heated to 1400° C. to vaporize, and then condensed on a collecting plate at 400° C. to obtain magnesium-doped silicon oxide.
[0137] The magnesium-doped silicon oxide was heat-treated at a temperature of 900° C. in an argon (Ar) atmosphere for 15 hours to prepare a cathode material for a secondary battery in a bulk form.
[0138] The prepared bulk secondary battery cathode material is mechanically crushed into an average particle size of 5 μm to prepare a granular cathode material, and the granular cathode material is coated with carbon at 5 weight percent using hydrocarbon gas and a CVD process at 850°C to prepare a cathode material powder coated with carbon.
[0139] Comparative Example 1
[0140] The raw materials of Si, SiO2 and MgO were respectively put into a powder mixer at a molar ratio of 6 (Si): 4.5 (SiO2): 1.5 (MgO), and then uniformly mixed to prepare the raw materials.
[0141] After 26 kg of the above raw materials were placed in a crucible in a vacuum chamber of less than 0.1 Torr, they were heated to 1400°C to gasify them, and then condensed on a collecting plate at 400°C to obtain magnesium-doped silicon oxide. The obtained magnesium-doped silicon oxide (cathode material for bulk secondary batteries) was mechanically crushed into an average particle size of 5 μm to prepare a granular cathode material, and carbon was coated on the granular cathode material at 5 weight percent using hydrocarbon gas and a CVD process at 850°C to prepare a cathode material powder coated with carbon.
[0142] Comparative Example 2
[0143] 24 kg of a mixed raw material of Si and SiO2 was placed in crucible A, and 2 kg of a metal Mg block was placed in crucible B. Crucible A and crucible B were heated to 1500°C and 900°C respectively, and then condensed on a collecting plate at 900°C to obtain magnesium-doped silicon oxide.
[0144] The obtained magnesium-doped silicon oxide (cathode material for bulk secondary batteries) was mechanically crushed into an average particle size of 5 μm to prepare a granular cathode material, and carbon was coated on the granular cathode material at 5 weight percent using hydrocarbon gas and a CVD process at 850°C to prepare a cathode material powder coated with carbon.
[0145] Experimental example
[0146] Deviation of Mg content
[0147] like Figure 1 As shown, the cross section across the center of the magnesium-doped silicon oxide before pulverization (Comparative Example 2) or the bulk secondary battery cathode material obtained by heat treatment (Example) is used as a reference, and the average content (weight percentage) of the doping element calculated by detecting any 100 points in the spectral line profile across the center of the cross section by energy dispersive X-ray spectroscopy is taken as A, and the standard deviation of the content is taken as B. As a result of component analysis, the B / A of the cathode material sample prepared in the Example is 0.1, and the B / A of Comparative Example 2 is 0.43.
[0148] Raman analysis
[0149] The Raman signal of silicon analyzed by μ-Raman (equipment name: XperRam C, NANOBASE, Korea) of the pulverized cathode material was used as a reference, and Raman analysis was performed under the following conditions. Figure 2 As shown. Figure 2 As shown, the Raman signal (peak center) of silicon of the cathode material prepared in the embodiment is 523.6 cm -1, has residual compressive stress, while the cathode material prepared in the comparative example has residual tensile stress. In addition, the detection result of the half-maximum width of the Raman signal of the silicon prepared in the embodiment confirmed that the half-maximum width was 12 cm -1 , which is larger than the full width at half maximum of the Raman signal of single-crystalline silicon (C-Si (ref) in the figure).
[0150] Analysis conditions: excitation laser wavelength 532nm, laser power 0.5mW, spectrometer resolution 1cm -1 , 1 g of powdered cathode material, and the detector exposure time is 15 seconds (s).
[0151] The stress remaining in silicon was calculated using the Raman detection results and the following formula, and the residual stress of silicon in the granular cathode material and the residual stress of silicon in the bulk cathode material are shown in Table 1. As listed in Table 1 together with the results of the comparative examples, in the case of the cathode material prepared in the embodiment, silicon has a residual compressive stress of 0.7 GPa in the bulk form and a residual compressive stress of 0.25 GPa in the granular form, while in the case of Comparative Example 1, Si is amorphous, and in the case of Comparative Example 2, Si has no compressive stress but has tensile stress.
[0152] σ(MPa)=-500×Δω(cm -1 )
[0153] Where σ is the residual stress, Δω is the Raman signal of the sample tested and the Raman signal of single crystal silicon (C-Si (ref) in the figure, 520.4 cm -1 ) (= detected Raman signal wave number of silicon - Raman signal wave number of single crystal silicon). If σ is a positive value, it indicates compressive stress, and if it is a negative value, it indicates tensile stress.
[0154] Under the following conditions, two-dimensional mapping analysis was performed based on the Raman signal of silicon of the magnesium-doped silicon oxide before pulverization (comparative example) or the bulk secondary battery cathode material obtained by heat treatment (example) μ-Raman analysis (equipment name: XperRam C, NANOBASE, South Korea). The mapping results are as follows: Figure 3 In the case of the cathode material prepared in the example, the Raman peak of silicon is detected in all pixels, and the offset of each pixel is detected = WN i (Si)-WN(ref), it was confirmed that the shift ranged from 2.86 (minimum value) to 4.58 (maximum value).
[0155] Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) = 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm-1 , map size = 14 μm × 14 μm.
[0156] Mechanical properties
[0157] In order to test the particle strength and particle expansion, the micro compression tester MCT-W produced by Shimadzu Corporation was used to test the compression strength. The particle strength of any 10 particles with a diameter of 10 μm was tested, and the test results are shown in Table 1.
[0158] The micro compression tester continuously applies force to the particles, defines the pressure at which the particles break as the particle strength, and automatically detects it.
[0159] The cross-section of magnesium-doped silicon oxide before crushing (Comparative Example 1) or the bulk secondary battery cathode material obtained by heat treatment (Example) was used as the object, and the test was carried out using a nanoindentation tester (Anton Paar, Austria). In the case of the nanoindentation test (indenter), according to the test standard of ISO14577-1E, the test conditions are to use a Bosch indenter with a Poisson's ratio assumed to be 0.3, a maximum load of 50mN, and a load application speed of 100mN / min. In this case, based on the indentation caused by the indenter, the distance between the indentations is at least 10μm, and the test is carried out in the form of a matrix of 5×5 to 25×25. The strength and Young's modulus calculated in this way are as follows: Figure 4 shown.
[0160] Preparation of batteries
[0161] The final cathode material powder is used as an active material, and the active material, conductive material (carbon black), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR) are mixed in a weight ratio of 8:1:0.5:0.5 and a solvent is added to prepare a slurry, which is then applied to a copper foil with a thickness of 17μm and dried at a temperature of 90°C for 40 minutes. After drying, it is punched into a diameter of 14mm, a metal lithium with a diameter of 16mm is used as a counter electrode, and a separation membrane with a diameter of 18mm is placed between them and filled with electrolyte to prepare a CR2032 button half-cell. 1M LiPF6 is dissolved in a solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) mixed in a volume ratio of 1:1 to use as an electrolyte, and 3 weight percent of fluoroethylene carbonate (FEC) is added as an additive. The formation process is carried out by the following steps: the prepared battery is charged (lithiation) to 0.005V at a constant current of 0.1C, charged at a constant voltage of 0.005V until it reaches 0.01C, and then discharged (de-lithiation) to 1.5V at a constant current of 0.1C (first formation step); thereafter, it is charged (lithiation) to 0.005V at a constant current of 0.1C again, charged at a constant voltage of 0.005V until it reaches 0.01C, and then discharged (de-lithiation) to 1.0V at a constant current of 0.1C (second formation step).
[0162] Evaluating battery performance
[0163] The charge and discharge cycle conditions were as follows: charging (lithiation) at a constant current of 0.5C to 0.005V, charging at a constant voltage of 0.005V until reaching 0.05C, and then discharging (de-lithiation) at a constant current of 0.5C to 1.0V.
[0164] Charge and discharge cycle times: 50 times
[0165] The discharge capacity of the first charge-discharge cycle is expressed as capacity in Table 1. The initial efficiency based on the charge-discharge in the first formation step and the capacity retention rate of C50 / C1×100 are shown in Table 1. The curve diagram of the charge and discharge capacity according to the first formation step, the second formation step and the charge-discharge cycle is shown in Figure 5 shown.
[0166] Table 1
[0167] Example 1 Comparative Example 1 Comparative Example 2 Average Mg content A(%) 7.1 7.2 4.0 Standard Deviation B 0.78 0.81 1.71 Compressive stress of block (GPa) 0.7 Amorphous -0.4 Compressive stress of powder (GPa) 0.25 Amorphous -0.9 Particle compressive strength (GPa) 0.164 0.116 0.096 Capacity (mAh / g) 1406 1,394 1382 Efficiency (%) 82.2 59.4 75.3 Capacity retention rate (%) 96.4 67.4 55.8
[0168] Figure 6 In order to observe the high-resolution transmission electron microscopy photos of the cathode materials prepared in the examples, Figure 6 It can be seen that the average diameter of crystalline silicon nanoparticles is about 6.7nm. Figure 7 A high-resolution transmission electron micrograph of the observed substrate and a selected area diffraction pattern of the area indicated by the yellow circle are shown in the upper insert. Figure 6 and Figure 7 The results of high-resolution transmission electron microscopy (HR-TEM) and selected area diffraction pattern analysis confirmed that the matrix contained crystalline magnesium silicate and that the silicon nanoparticles formed a coherent interface with the crystalline magnesium silicate.
[0169] Figure 8 The following are scanning electron microscope photos of the cross section and thickness of the cathode before lithiation and the cross section and thickness of the cathode after lithiation at 0.005 V in the third charge-discharge cycle (the first charge-discharge cycle in the life evaluation step). The volume expansion rate was confirmed to be only 15% by the thickness change before and after lithiation.
[0170] Fig. 9 The graph showing the particle size distribution of the cathode material powder pulverized and coated with carbon measured shows that the average particle size (D50) was 8.3 μm.
[0171] Fig.10 dQ / dV curve diagram in the first charge and discharge cycle. Fig.10 It can be seen that there exists a 3.75 The lithium insertion peak of Si reaction. It can be seen that the cathode material prepared in the embodiment is lithiated at a ratio of 3.75 moles of lithium per mole of silicon.
[0172] Fig.11 This is a diagram showing the selected area diffraction pattern of the cathode material charged to 0.005V in the first charge-discharge cycle observed using a transmission electron microscope, and selectively analyzing only the lithiated silicon nanoparticles. Fig.11 It can be directly confirmed that Li 3.75 Si reaction, which is Fig.10 The dQ / dV curve results are consistent with those of
[0173] As described above, although the present invention is described with specific matters, limited embodiments and drawings, these are only provided to help to more fully understand the present invention. The present invention is not limited to the above embodiments, and ordinary technicians in the technical field to which the present invention belongs can make various modifications and deformations through the above description.
[0174] Therefore, the concept of the present invention is not limited to the illustrated embodiments, and not only the scope of protection of the accompanying invention claims, but also modifications that are equal or equivalent to the scope of protection of the invention claims should fall within the scope of the concept of the present invention.
Claims
1. A cathode material for a secondary battery, characterized in that: Include: a substrate comprising silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof; and Silicon nanoparticles are dispersed and embedded in the matrix and have residual compressive stress.
2. A cathode material for a secondary battery, characterized in that: Include: a substrate comprising silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof; and Silicon nanoparticles are dispersed and embedded in the above matrix and have residual compressive stress. The above-mentioned cathode material for secondary battery satisfies the following formula 1: Formula 1: 1<WN(Si) / WN(ref), In Formula 1, WN(ref) is the center wave number of the Raman peak of bulk single crystal silicon, and WN(Si) is the center wave number of the Raman peak of nano-particulate silicon contained in the cathode material.
3. The cathode material for secondary battery according to claim 2, characterized in that: The difference between WN(Si) and WN(ref) is 0.1cm -1 above.
4. The cathode material for secondary battery according to claim 2, characterized in that: The full width at half maximum of the Raman peak of the nanoparticulate silicon contained in the cathode material is larger than the full width at half maximum of the Raman peak of bulk single crystal silicon.
5. The cathode material for secondary battery according to claim 2, characterized in that: The full width at half maximum of the Raman peak of the nanoparticle-shaped silicon contained in the cathode material is 4 cm -1 Up to 20cm -1 .
6. The cathode material for secondary battery according to claim 2, characterized in that: When two-dimensional mapping analysis is performed based on the Raman signal of silicon, the difference between the maximum and minimum values of the shift specified by the following equation 2 under the following mapping conditions is 5 cm -1 the following, Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time = 1 s, i.e. exposure time per unit analysis area = 1 s, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1 , map size = 14 μm × 14 μm, Formula 2: Offset = WN i (Si)-WN(ref), In formula 2, WN(ref) is the same as in formula 1, WN i (Si) is the center wave number of the Raman peak of nanoparticulate silicon contained in the cathode material in one pixel as a unit analysis area in mapping analysis.
7. A cathode material for a secondary battery, characterized in that: Include: a substrate comprising silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof; and Silicon nanoparticles are dispersed and embedded in the above matrix and have residual compressive stress. The strength of the cathode material for the secondary battery measured by a nanoindentation test is 4.0 GPa or more, and the Young's modulus is 40 MPa or more.
8. A cathode material for a secondary battery, characterized in that: The cathode material of the secondary battery is in the form of particles containing the following substances: a substrate comprising silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof; and Silicon nanoparticles are dispersed and embedded in the above matrix and have residual compressive stress. The compressive strength of the particles is 100 MPa or more.
9. A cathode material for a secondary battery, characterized in that: Include: a matrix comprising, based on elemental composition, silicon, one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, and oxygen; and Silicon nanoparticles are dispersed and embedded in the above matrix and have residual compressive stress. The cathode material for secondary battery has a composition uniformity satisfying the following formula 3: Formula 3: B / A≤0.30, In Formula 3, A and B are respectively the average value (A) and standard deviation (B) of the content of the doping element detected at any 100 points based on a cross section passing through the center of the cathode material, and the unit of the above content is weight percentage.
10. The cathode material for secondary battery according to claim 9, characterized in that Based on the compound composition, the above matrix includes: Silicon oxide; and Composite oxides of the above doping elements and silicon.
11. A cathode material for a secondary battery, characterized in that: Include: a substrate comprising silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof; and Silicon nanoparticles are dispersed and embedded in the above matrix and have residual compressive stress. When the cathode active material layer having 80 weight percent of the active material including the cathode material, 10 weight percent of the conductive material and 10 weight percent of the binder is charged to 0.005 V, the volume change of the cathode active material layer is within 60%.
12. A cathode material for a secondary battery, characterized in that: Include: a substrate comprising silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof; and Silicon nanoparticles are dispersed and embedded in the above matrix and have residual compressive stress. According to the following charge and discharge cycle conditions, when the half-cell with the counter electrode being a metal lithium foil is used for charge and discharge testing, the dQ / dV curve obtained has a Li 3.75 The lithium insertion peak of Si reaction has a discharge capacity of more than 1200 mAh / g in the first charge and discharge cycle. Charge and discharge cycle conditions: constant current / constant voltage, cut-off voltage of 0.005V~1.0V, charging rate of 0.
5.
13. A cathode material for a secondary battery, characterized in that: Include: a substrate comprising silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof; and Silicon nanoparticles are dispersed and embedded in the above matrix and have residual compressive stress. When the charge and discharge test is performed using a half-cell with a metal lithium foil as the electrode according to the following charge and discharge cycle conditions, Formula 4 is satisfied: Charge and discharge cycle conditions: constant current / constant voltage, cut-off voltage 0.005V~1.0V, charging rate 0.5, Formula 4: 95% ≤ C50 / C1×100, In Formula 4, C1 is the discharge capacity in the first charge-discharge cycle, in mAh / g, and C50 is the discharge capacity in the 50th charge-discharge cycle.
14. The cathode material for secondary battery according to claim 13, characterized in that: C50 is 1200 mAh / g or more.
15. The cathode material for a secondary battery according to any one of claims 1 to 14, characterized in that The average diameter of the silicon nanoparticles is 2 nm to 30 nm.
16. The cathode material for a secondary battery according to any one of claims 1 to 14, characterized in that: The interface between the silicon nanoparticles and the substrate is a coherent interface.
17. The cathode material for a secondary battery according to any one of claims 1 to 14, characterized in that The doping element is at least one selected from lithium, sodium, potassium, rubidium, cesium, beryllium, magnesium, calcium, strontium and barium.
18. The cathode material for a secondary battery according to any one of claims 1 to 14, characterized in that The above-mentioned complex oxide includes crystals.
19. The cathode material for a secondary battery according to any one of claims 1 to 14, characterized in that The cathode material has an average diameter of 10 0 μm to 10 1 μm-level particles.
20. The cathode material for a secondary battery according to any one of claims 1 to 14, characterized in that The cathode material further includes a coating layer containing carbon.
21. A cathode, characterized in that: The secondary battery cathode material according to any one of claims 1 to 14 is included.
22. A secondary battery, characterized in that: Comprising the cathode according to claim 21.
Citation Information
Patent Citations
Anode active material, anode including the anode active material, and lithium secondary battery including the anode
KR1020150045336A
Silicon-based composite anode active material for secondary battery, negative electrode comprising same
KR1020200065514A
Silicon oxide based negative electrode material
JP2017224600A
KR20190116012A